PSYCHOLOGICAL AND PEDAGOGICAL SUPPORT FOR PERSONAL SELF-DEVELOPMENT OF STUDENTS IN THE PROCESS HIGHER EDUCATION (Pedagogy of Higher and Secondary Education, 2009)
The article deals with the peculiarities of psychological and pedagogical support of students' personal own development in the process of interactive training.
Keywords: psychological and pedagogical; own development; interactive training